Effectiveness of the Bakiak Game in Improving Peer Interaction among Elementary School Students - Satrio Wahyudi; Indra Safari; Rizal Ahmad Fauzi (Universitas Negeri Semarang, 2026)
This study aims to determine the effectiveness of the bakiak (clog) game in improving peer interaction among grade V students of SDN Pasirbenteng II. The research employed a quantitative approach with a pre-experimental method through a one group pretest–posttest design. The research sample consisted of 37 students selected using the total sampling technique. The research instrument was a peer interaction questionnaire based on indicators of cooperation, communication, empathy, tolerance, and social support, comprising 19 statement items. Prior to use, the instrument underwent validity and reliability testing. The reliability test using Cronbach's Alpha yielded a value of α = 0.720, indicating that the instrument is reliable. Item validity was assessed using corrected item-total correlation, resulting in 11 valid items out of 19, which were retained for data collection. Data analysis used descriptive statistics, N-Gain calculations, and the Paired Sample t-Test. The results showed that the average score increased from 54.81 (pretest) to 90.59 (posttest), with an average N-Gain value of 0.7886, categorized as high. The Paired Sample t-Test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. These findings demonstrate that the bakiak game is effective in improving peer interaction among elementary school students.